The Effect of Various Parameters on Measuring Alpha and Beta Particles from Soil Sample; An Environmental Dosimetry - Torshabi, Ahmad Esmaili; Mohammadzadeh, Sepideh (Frontiers in biomedical technologies, 2025)
Purpose: The measurement of natural radioactive decay in environmental samples such as soil has received increasing importance in recent years. Proportional counters in the form of large-area planar detectors are widely used for the initial screening of  radioactivity in environmental samples. In this study, the affecting factors in the alpha and beta particles emitted from natural radioactive soil sample was simulated using the Monte Carlo FLUKA code. Materials and Methods: These factors include the thickness of the sample, source-detector air gap, Mylar thickness, and gas detector density. Simulations were performed for alpha particles in 4.8 MeV and in the conventional range for the investigation of radioactive elements inside the soil sample. Results: The final analyzed results show that the maximum number of primary particles can be measured up to 5 and 100 µm of soil sample thickness for alpha and beta particles, respectively. The maximum counting efficiencies for alpha and beta particles are 23% and 42%, respectively for our simulated sample. Conclusion: For alpha particles, gas detector density variations have no effect on the efficiency. For beta particles, this efficiency is constant up to 0.0005 g/  density of gas. Furthermore, by increasing the air gap and Mylar thickness the efficiency will be decreased for both alpha and beta particles, while the variation of this value is remarkable for alpha particles.